Human Aspects in Software Engineering: Challenges, best practices and future direction (International Journal of Food and Nutritional Sciences, 2022)
Software engineering, at its core, is a collaborative effort pushed by way of human ingenuity,verbal exchange, and innovation. This overview paper gives a comprehensive exploration of thepivotal position played by using human factors in software program engineering approaches.